Essays on competition and technical efficiencies in South Africa’s medical scheme industry - Ndlovu, Thabang (My University, 2022)
According to existing economic literature there are idiosyncratic elements within healthcare markets that prevent normal market forces, such as competition, to shape the healthcare industry in the same manner as other industries. The reasons for this are regulatory barries to entry, fixed costs, the role of insurance, information frictions and asymmetries. More so, the healthcare sector is comprised of various interconnected sub-sectors that all have their own institutions and nuances. In the South African Context, the Health Market Inquiry, which was conducted by the Competition Commission of South Africa, submit that the South African healthcare sector comprises a complex set of interrelated stakeholders that interact in markets that are not transparent and not quite understood. Given this, the primary objective of conducting this doctoral study was to understand the competition and efficiency dynamics within South African healthcare insurer markets through a collection of related empirical papers on competition and efficiency. Annual firm level data on South African medical schemes was used to study various economic theories using panel data econometric techniques. The results suggest that open medical schemes tended to be more efficient than restricted medical schemes in terms of technical, scale and pure technical efficiency over the sample period. More so, the empirical results reveal that there is room for improvement in terms of efficiencies for both open and restricted medical schemes. This is specifically true for restricted medical schemes. In addition, the empirical results seem to support the view that firms with market power, operating in highly concentrated markets, will limit competition and will operate under a reduced efficiency level. Further, the empirical results revealed that both the structureconduct-performance and efficient structure hypotheses can be rejected in relation to South African medical schemes. The empirical evidence further suggests support for differing hypotheses for open and restricted medical schemes when traditional structural approaches to assessing competition are employed. Moreover, the empirical evidence suggests that the market for restricted medical schemes is highly concentrated and operating under a reduced efficiency level which produces less than desirable outcomes. These findings are supported when nonstructural approaches to competition are employed as the empirical results from the nonstructural approaches to assessing competition suggest that both open and restricted medical schemes are operating under conditions of monopolistic competition. Furthermore, once efficiency is incorporated in the model, the empirical findings still reveal conditions of monopolistic competition
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2022
Keywords: Medical Scheme Industry; Healthcare markets; South Africa